Disease perception and experiences among rural Bangladeshi hypertensive women: A qualitative approach - Yasmin Jahan; Michiko Moriyama; Md Moshiur Rahman; Kana Kazawa; Mariko Mizukawa; Atiqur Rahman; Abu Sadat Mohammad Sayeem Bin Shahid; Sumon Kumar Das; Abu Syed Golam Faruque; Mohammod Jobayer Chisti (Tabriz University of Medical Sciences, 2020)
Background: Hypertension (HTN) is well established as a leading cause of common serious illnesses worldwide. We carried out this qualitative research to understand perception of and experiences related to HTN among rural Bangladeshi hypertensive women. Methods: A total of 74 female hypertensive participants who were diagnosed as HTN were purposively recruited in a rural community in Mirzapur, Bangladesh. A focus group discussion(FGD) was applied to share their perception and experiences. Transcripts were read in an iterative process, and a thematic analysis was performed. This paper is reported followed by COREQ checklist. Results: Three main themes were generated; (i) Perception of HTN based on experiences, (ii)Knowledge of management of HTN, and (iii) Barriers of management of HTN. Under the themes, seven subthemes were identified. The participants only knew about their high blood pressure(HBP) when they had symptoms, and they applied traditional remedies in the rural context to deal with those symptoms. Even though more than half of participants had relevant knowledge of how to manage HTN, but still there were social-cultural and economic barriers and lack of social infrastructure to access healthcare, existed to practice them. Conclusion: Based on our study reports, health education programs at the household and community level could be a potential starting point for any preventive and containment strategy in rural communities of Bangladesh.